Determination of pH, Ammonia and Nitrate Level in Ghodaghodi Lake, Jokhar Lake and Geta Fisheries - Ojha, Manoj (AMC Journal (Dhangadhi), 2025)
The main aim of this research is to check the water quality for domestic purposes and survival of aquatic species. The present study was conducted in two representative lakes Ghodaghodi and Jokhar Lake of Kailali district and one Geta Fisheries. A total of 10 samples were collected from Ghodaghodi Lake, Jokhar Lake and Geta Fisheries and analyzed for water pH, ammonia and nitrate level in the pre monsoon season during 2024. The pH of water samples was determined by using bench top pH meter. It was found that Ghodaghodi Lake and Geta Fisheries were moderately alkaline and pH ranges from (7.0 -9.7) and (8.2- 9.6) respectively. The pH of Jokhar Lake was found to be in the range of (6.3-8.1).The concentration of ammonia was found to be higher in Jokhar Lake which ranges from (0.1-0.32) mg/L in comparison to Ghodaghodi Lake (0.1-0.17) mg/L and Geta Fisheries (0.15-0.16) mg/L. On the other hand, the concentration of nitrate was found to be ranges from (3-5) mg/L in Ghodaghodi Lake and (2-3) mg/L in Geta Fisheries. The nitrate content was somewhat high in Jokhar Lake ranges from (5-7) mg/L. The pH range is 6.5–8.5, ammonia limit is 1.5 mg/L, and nitrate limit is 50 mg/L in both WHO 2019 and NDWQS 2023 standards. While comparing the different parameter with WHO and NDWQS 2079 drinking water guidelines, these three lakes, Ghodaghodi Lake, Jokhar Lake, and Geta Fisheries, were within the permissible limit standards for safe drinking water and aquaculture. Among all three, Geta Fisheries demonstrated the most stable water quality parameters across all measured indicators with score of 9±0.72 for pH, 0.15 ±0.005 for ammonia and 2.33±0.57 for nitrate. Overall, the lakes were relatively unpolluted and suitable for drinking purposes and fish farming but, special steps were taken in consideration to protect the lakes in their pristine conditions in the future.